Dating modern deltas: progress, problems and prognostics - Stanley, D. J. (Annual Review of Earth and Atmospheric Sciences, 2001)
Radiocarbon dating is the method most frequently used to date Holocene deltaic sequences, but less than one quarter of 14C dates are within ±500 years of predicted age. Such dates tend to be unreliable, in other words, often too old and commonly inverted upsection, and core sample dates obtained near deltaic plain surfaces may be as old as mid- to late Holocene. Stratigraphic irregularities result primarily from downslope reworking of upland alluvial sediment, with displacement of “old carbon” in the sediment that accumulates in lower valleys and deltaic plains. Use of dates that are too old results in inaccurately calculated rates (most often too low) of relative sea-level rise and/or land subsidence. More reliable timing of deltaic sediment requires a multiple-method dating approach, including, where possible, identification of associated archaeological material. Developing an accurate dating strategy is a critical step for implementing reliable coastal protection measures needed for the rapidly increasing human populations in these low-lying, vulnerable nearshore settings.
id: 1378